Advancing the Liberal Order in British Columbia: The Role Played by Lieutenant-Governor Sir Hector-Gustave Joly de Lotbinière, 1900–1906 - Little, J. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractThis essay focuses on the role of Lieutenant-Governor Hector-Gustave Joly de Lotbinière in bringing political stability to British Columbia after the turn of the twentieth century. As well as ensuring that the composition of the executive council was based on federal party lines, he worked to ease federal-provincial tensions and exercised a significant influence on the McBride government’s highly effective economic reform programme. Joly has been largely ignored by historians, aside from his short term as Quebec premier, but his socially conservative liberalism made him an ideal promoter of Canada’s liberal order on the west coast.